Plasma enhanced layer-by-layer deposition and nanocrystallization of hydrogenated amorphous silicon films - Chen, Zhuo; Mucha, John A.; Donnelly, Vincent M.; Economou, Demetre J. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2013)
A layer-by-layer technique, using a reactor with two separate plasma sources, was developed for a-Si:H deposition and nanocrystallization. Substrates were heated to 250 °C and rotated between the two plasma sources, with selectable residence times in each source. A SiH4/He/H2 capacitively coupled plasma (CCP) was employed to deposit a thin a-Si:H layer that was subsequently exposed to a H2 inductively coupled plasma (ICP) to induce crystallization in the layer. The cycle of deposition followed by nanocrystallization was repeated to grow thin films with different volume fractions (from 0% to 72%) of crystalline material, as determined by Raman spectroscopy. For the same total exposure time in the CCP, many short exposures (i.e., more cycles) were more effective in producing nanocrystalline Si compared to few long exposures. In addition, for a given number of cycles, the fraction of nanocrystalline Si increased with increasing ICP-to-CCP exposure time ratio (which ranged from 1/4 to 4/1). Transmission electron microscopy revealed crystallites with columnar structure along the film growth direction. Mass spectrometric monitoring of a dominant reaction product emanating from films grown in the CCP and subsequently exposed to a D2 ICP suggested that etching and structural reorganization during nanocrystallization occurred throughout the film volume.